GONAD OF THE PROTANDRIC PRAWN HIPPOLYSMATA ENSIROSTRIS KEMP - Sukumaran, K K (Indian Journal of Fisheries, 2011)
to Hippolysmata ensirostris the gonad is a true testfe with a pair of vasdeferens in males. In females, the gonad is an ovotestis and consists of an anteriorovarian portion' and1 a posterior tesrtibulair pontiion. The testiicuSair porttan thoughpresent in all females, Â«s> in a State of atrophy. However, the testicular portioncontains sperans. A pair of wis deferens is present fa active females in adiditkMi tooviducts.